Cost-effectiveness of oral versus intravenous antibiotics (OVIVA) in patients with bone and joint infection: evidence from a non-inferiority trial - OVIVA collaborators; McMeekin, N; Geue, C; Briggs, A; Rombach, I; Li, H; Bejon, P; McNally, M; Atkins, B; Ferguson, J; Scarborough, M (F1000, 2019)
Background: Bone and joint infections are becoming increasingly common and are usually treated with surgery and a course of intravenous antibiotics. However, there is no evidence to support the superiority of intravenous therapy and there is a growing body of literature showing that oral therapy is effective in treating these infections. Given this lack of evidence the clinical trial ‘Oral Versus Intravenous Antibiotics’ (OVIVA) was designed to assess the clinical and cost-effectiveness of intravenous versus oral antibiotics for the treatment of bone and joint infections, using a non-inferiority design. Clinical results from the trial indicate that oral antibiotics are non-inferior to intravenous antibiotics. The aim of this paper is to evaluate the cost-effectiveness of intravenous compared to oral antibiotics for treating bone and joint infections, using data from OVIVA.